Efficacy of naproxen in the management of patients hospitalized with COVID-19 infection: A randomized, double-blind, placebo-controlled, clinical trial. Issue 6 (November 2021) - Asadi, Masoomeh; Sayar, Sara; Radmanesh, Esmat; Naghshi, Sina; Mousaviasl, Sajedeh; Jelvay, Saeed; Ebrahimzadeh, Mona; Mohammadi, Asma; Abbasi, Samaneh; Mobarak, Sara; Bitaraf, Saeid; Zardehmehri, Fatemeh; et al.
Abstract: Background and aims: The current study was done to examine the efficacy of naproxen in the management of patients with COVID-19 infection. Methods: This randomized, double-blind, placebo-controlled, clinical trial was done on hospitalized adult patients with confirmed COVID-19 infection. Patients were randomly assigned to receive either naproxen (two capsules per day each containing 500 mg naproxen sodium) or placebo (containing starch) for five days along with the routine treatment that was nationally recommended for COVID-19 infection. Clinical symptoms of COVID-19 infection, the time to clinical improvement, blood pressure, laboratory parameters, and death due to COVID-19 infection were considered as the outcome variables in the present study. Results: Treatment with naproxen improved cough and shortness of breath in COVID-19 patients; such that, compared with placebo, naproxen intake was associated with 2.90 (95% CI: 1.10–7.66) and 2.82 (95% CI: 1.05–7.55) times more improvement in cough and shortness of breath, respectively. In addition, naproxen administration resulted in a significant increase in mean corpuscular volume (MCV) and had a preventive effect on the reduction of systolic blood pressure in COVID-19 patients. Conclusion: Treatment with naproxen can improve cough and shortness of breath in COVID-19-infected patients. Further studies are required to confirm our findings. Highlights: Treatment with naproxen can improve cough and shortness of breath in COVID-19-infected patients. Naproxen administration has a preventive effect on the reduction of systolic blood pressure in COVID-19 patients. Naproxen treatment did not have any effect on mortality in COVID-19 patients.